The status and potential of renewable energy development in Jordan: exploring challenges and opportunities - Salah A.A.; Shalby M.M.; Basim Ismail F. (Taylor and Francis Ltd., 2024)
The energy sector poses one of the largest challenges for the Jordanian economy because it directly influences economic growth. The countrys high dependence on imported intensive fossil-fuel sources (93% in 2021) has overburdened the national budget. The government has therefore defined a set of priorities and actions based on greater utilization of domestic resources, including renewable energy. The capacity of renewable energy systems feeding into the power grid in Jordan reached 2,445 megawatts (MW) in 2021, approximately 20% of the national electricity mix. This article investigates the capacity of renewable energy in Jordan and analyzes the present state of its renewable energy industry, which can aid decision makers and investors in developing plans for future projects. The country is taking steps to address several obstacles facing the energy sector including upgrading the grid, exporting excess electricity generated from renewables to international markets, and developing new policies and regulations for renewable energy growth. Jordan has significant potential to succeed in scaling up its use of renewables, particularly in electricity generation, which could reduce energy prices for consumers and improve energy security. The article also discusses opportunities in the renewable energy industry in Jordan and outlines next steps including reducing domestic greenhouse-gas emissions. 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.